EFFECT OF SINTERING UNDER HIGH TEMPERATURES AND PRESSURE AND MECHANICAL ALLOYING ON THE CRYSTAL STRUCTURE OF THE TiC, ZrC, HfC MONOCARBIDES - Belyavina, N.M.; Turkevich, V.Z.; Kuryliuk, A.M.; Stratiichuk, D.A.; Nakonechna, O.I.; Kogutyuk, P.P.; Stasuk, L.P. (Reports of the National Academy of Sciences of Ukraine, 2023)
The phase composition of the HPHT sintering products (7.7 GPa, 1600-2450 °C) of the cBN—TiC—Al, cBN—ZrC—Al, and cBN—HfC—Al systems (with a volume ratio of charge components of 60 : 35 : 5) was studied using the X-ray diffraction method. It was observed that solid-state reactions in these systems initiate at barothermal treatment temperatures above 2000 °C, leading to the formation of MeB2 borides (Me = Ti, Zr, or Hf) and AlN nitride. The crystal structure peculiarities of the individual phases formed in the HPHT sintering products were investigated. It was found that MeB2 borides incorporate a small amount of aluminum, while the initial MeC carbides transform into Me1–xAlxC solid solutions, with TiC, ZrC, and HfC containing ≈ 8, 7 and 6 % atomic percent of Al, respectively. The accumulation of aluminum atoms in the Me1–xAlxC solid solutions occurs through the preliminary formation of Me vacancies, the quantity of which correlates with the enthalpy of formation of the initial MeC carbides.